The Effect of The Implementation Of The Tobacco Plain Packaging Act IndonesiaAustralia Policy Using The Dispute Settlement Behavior Analysis Unit - Fersa, Syurahbil Fachrezy; Setiawan, Yohanes Alga; Al Ghozy, Faturrahman; Mulawwani, Mahira (JLAST : Journal of Law and Social Transformation, 2024)
In 2011, the Australian Parliament had the opportunity to enact the Tobacco PlainPackaging Act, also known as the TPP Act. Because of this piece of legislation, the packagingof all tobacco products is required to be completely free of any trademarks, logos, or images.Indonesia, which is the nation that produces the most tobacco in the world, has challengedthe decision made by Australia and has begun legal processes with the World TradeOrganization (WTO). The purpose of this study is to investigate the strategy that the nationhas taken to deal with the problem that has arisen as a result of the TPP Act. A literaturestudy is the research approach that was utilized in this report. This methodology entailsreading and gathering data from journal sources, articles, and other relevant literaturesources that are related to the topic matter.